Story therapy on children's anxiety that treated in hospital - Eko Suryani; Maria H Bakrie (Jurnal Kesehatan Ibu dan Anak, 2021)
Hospitalization will bring some psychological changes in the child. One effort that can be done to reduce anxiety is through play therapy. This study aims to determine the influence of story therapy on children who hospitalized. This study was a quasi-experimental design. The observations is made twice to compare and determine  the patient’s anxiety children performed by picture story and without picture story therapy. There were differences between the treatment group and the control group before (p-value = 0.141) and after the treatment (p-value = 0.033) of story therapy treatment in pediatric patients. Story therapy can reduce children's anxiety while being treated in hospital.